Dimensi Humantitarian dalam Sistem Ekonomi Islam - Rahmani Timorita Yuliant (Millah: Journal of Religious Studies, 2005)
Islamic economic system has divinity and humanity moral character. Islam has an economic system which applies resources given by Allah to meet the basic needs of human and gives them good life. Based on this view, the writer stresses that Islamic economic system needs to be fulfilled by human dimension in all fields of economic such as production, consumption, distribution, and circulation. On this frame, this article tries to identify the application of humanity principles into Islamic economic system related to activities in production, consumption, distribution, and circulation field.